2019
DOI: 10.21831/jk.v3i2.23820
|View full text |Cite
|
Sign up to set email alerts
|

Blended Learning: The Effectiveness of Schoology Based E-Learning on Mathematic Communication Ability

Abstract: BLENDED LEARNING: KEEFEKTIFAN E-LEARNING BERBASIS SCHOOLOGY TERHADAP KEMAMPUAN KOMUNIKASI MATEMATISAbstrakPenelitian ini bertujuan untuk mengetahui efektivitas e-learning berbasis schoology terhadap kemampuan komunikasi matematis siswa SMP pada materi Sistem Persaman Linier Dua Variabel (SPLDV). Populasi penelitian adalah seluruh siswa kelas VIII salah satu SMP di Kota Cirebon. Sampel terdiri atas kelas VIII-B2 sebagai kelas eksperimen yang menerapkan schoology dan VIII-C2 sebagai kelas kontrol tanpa menggunak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
0
1
0
5
Order By: Relevance
“…Suriaman et al, (2019) state that learning via web-based instruction is a significant way to enhance the students' learning ability and willingness to participate in the classroom. Another research has shown that blended learning oriented to an online model without being limited by space positively impacts students (Setiyani, 2019). The use of this model shows an increase in the number of participation, graduation rates, and learning experiences because it uses technology IJEE (Indonesian Journal of English Education), 9 ( 1 that does not depend on specific modalities and mobility (Alsalhi, Eltahir, & Al-Qatawneh, 2019;Dziuban et al, 2018;Moura et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Suriaman et al, (2019) state that learning via web-based instruction is a significant way to enhance the students' learning ability and willingness to participate in the classroom. Another research has shown that blended learning oriented to an online model without being limited by space positively impacts students (Setiyani, 2019). The use of this model shows an increase in the number of participation, graduation rates, and learning experiences because it uses technology IJEE (Indonesian Journal of English Education), 9 ( 1 that does not depend on specific modalities and mobility (Alsalhi, Eltahir, & Al-Qatawneh, 2019;Dziuban et al, 2018;Moura et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Menurut (Setiyani, 2019), pada sebuah jurnal yang ditulisnya dengan judul "Blended Learning: Keefektifan E-Learning Berbasis Schoology terhadap Kemampuan Komunikasi Matematis". Jurnal tersebut berasal dari jurnal kependidikan, volume 3, nomor 2, pada bulan November 2019, dari Program Studi Pendidikan Matematika, Universitas Swadaya Gunung Jati.…”
Section: Hasil Dan Pembahasanunclassified
“…Schoology menurut Aminoto & Pathoni (2014) adalah website yang memadukan e-learning dan jejaring sosial. Setiyani (2019), mengungkapkan schoology merupakan situs yang berbentuk web sosial yang memberikan pembelajaran secara gratis sama seperti di dalam kelas dan media sosial.…”
Section: Janayu 12 Pendahuluanunclassified